Quality of Argumentation Questions on Excretory System Materials Using the ANATES Application - Ruri Lorika; Fitri Arsih; Heffi Alberida; Irdawati (LPPM Undiksha, 2024)
One of the relevant materials in this regard is the excretory system in biology learning, which requires students' deep understanding and problem-solving skills. However, developing valid, reliable, and quality argumentation questions for this material still faces challenges. This study evaluates the quality of argumentation questions on excretory system material using the ANATES application. A total of 35 grade XI students became research participants. The research instrument was in the form of 10 argumentation questions, which were analyzed using ANATES to measure the validity, reliability, difficulty level, and differentiating power of the questions. The analysis results provide a detailed explanation of the level of argumentation of questions on the material of the excretory system. In conclusion, this study underscores the critical role of item quality in accurately assessing student understanding. The findings advocate the continued use of ANATES to improve item construction. The implications of this study extend to educators and curriculum developers developing more effective assessment instruments. The findings of this study are expected to assist in creating more appropriate evaluation instruments to measure students' understanding of the excretory system material. In addition, the results of this analysis can also be used to improve and refine the types of questions to increase the validity and reliability of argumentation evaluation tools. To enhance the quality of science teaching in secondary schools, educators, curriculum designers, and educational researchers can utilize the implications of this study.